2018
DOI: 10.1016/j.jsps.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodination and biodistribution of newly synthesized 3-benzyl-2-([3-methoxybenzyl]thio)benzo[g]quinazolin-4-(3H)-one in tumor bearing mice

Abstract: 3-Benzyl-2-((3-methoxybenzyl)thio)benzo[g]quinazolin-4(3H)-one was previously synthesized and proved by physicochemical analyses (HRMS, 1H and 13C NMR). The target compound was examined for its radioactivity and the results showed that benzo[g]quinazoline was successfully labeled with radioactive iodine using NBS via an electrophilic substitution reaction. The reaction parameters that affected the labeling yield such as concentration, pH and time were studied to optimize the labeling conditions. The radiochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…4A with NS4A/NS4B as the representative peptide. In this study, a molecular modelling model was applied using the molecular operating environment (MOE), to clarify the activity of the targets (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and determine their probably bioactive conformations. We found important subsites for the HCV NS3/4A inhibition by three-dimensional telaprevir-complexed structure (PDB: 3SV6, resolution 1.4Å), 22 which was obtained from the PDB database, and the validation of the molecular docking protocol done by molecular redocking, with a position structure of RMSD lower than 2Å ( Fig.…”
Section: Docking Studymentioning
confidence: 99%
See 1 more Smart Citation
“…4A with NS4A/NS4B as the representative peptide. In this study, a molecular modelling model was applied using the molecular operating environment (MOE), to clarify the activity of the targets (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and determine their probably bioactive conformations. We found important subsites for the HCV NS3/4A inhibition by three-dimensional telaprevir-complexed structure (PDB: 3SV6, resolution 1.4Å), 22 which was obtained from the PDB database, and the validation of the molecular docking protocol done by molecular redocking, with a position structure of RMSD lower than 2Å ( Fig.…”
Section: Docking Studymentioning
confidence: 99%
“…7 Benzoquinazoline, a drug of immense research interest, has found a conspicuous place in medicinal chemistry owing to its diverse pharmacological properties. [15][16][17][18][19][20] Many benzoquinazolines were reported to show anti-HSV, -CVB4, viral activity and demonstrated promising 3C protease inhibition activity against HAV with IC 50 values of 3.30, 5.92, and 22.38 mM, respectively. 15,18 The results encouraged us to extend our research on benzoquinazolines chemistry to investigate their activity against HCV.…”
Section: Introductionmentioning
confidence: 99%
“…Benzoquinazolines, the basic components of numerous well-known heterocyclic systems, have played a significant role in the creation of various bioactive molecules. Extensive research conducted on benzoquinazolines in our lab has demonstrated their powerful pharmacological effects in a variety of contexts such as antioxidant, antimicrobial, anticancer and antidiabetic agents [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and particularly against a number of different viral infections as HSV-1, HSV-2, HAV, HCV and coxsackievirus B4 [ 30 , 31 , 32 ]. Through the analysis of our data, we were able to gather insights into the characteristics that will define future trials, which paved the path for the development of benzo[g]quinazolines as anti-human rotavirus Wa strain drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules featuring the benzo[ g ]quinazoline scaffold are widely studied in medicinal chemistry because of their numerous biological and chemical properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In our studies on benzo[ g ]quinazoline chemistry, many derivatives have been identified as potent α-glucosidase inhibitors with promising antidiabetic effects [ 17 ] and antimicrobial agents that show excellent activities against both Gram-positive and -negative bacteria along with strong antifungal activities [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[ h ]quinazolines have been reported as potent tyrosine kinase inhibitors that exhibit significant cytotoxicity against human carcinoma HT29, HCT116, and A549 cell lines [ 21 ], whereas benzo[ f ]quinazoline derivatives have been demonstrated to be potent thymidylate synthase inhibitors [ 22 ]. Moreover, benzo[ g ]quinazolines bearing sulfonamide, alkoxy, amino, and thioxo functional groups have shown high affinities toward the anaplastic lymphoma kinase receptor and demonstrate potent effects against EGFR and HER2 cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%